Evaluation of Stream Flow and Water Demand due to Climate Change in the Katha Basin Using Water Evaluation and Planning (WEAP) Model - Tun, Win Lwin; Cho Cho Thin Kyi; Yin Yin Htwe (The Indonesian Journal of Computer Science, 2024)
This study addresses the critical issue of assessing climate change impacts on streamflow and water demand in the Katha basin using the WEAP hydrological simulation model with the Soil Moisture (SM) method. The Katha basin, situated within Ayeyarwaddy River basin, faces variability in stream flow due to changing climatic conditions, impacting water availability for agriculture and domestic use. Through WEAP modeling, calibrated and validated against observed data from 2000-2012, the study projects an increase in annual flows under future scenarios (SSP245 and SSP585). Results indicate potential decreases in monsoonal flows, affecting water availability for agriculture and domestic use, necessitating adaptive management strategies. Model performance assessed by Nash Sutcliffe Efficiency (NSE) and Coefficient of Determination (R2) shows satisfactory agreement with observed data. The study underscores the urgency of integrated water resource management to sustainably address water demands amid climate variability, highlighting implications for agricultural productivity and water security in the region.